TRANSPARANSI DAN AKUNTABILITAS PEMERINTAH DESA DALAM PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDES) - Faridah, Faridah; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out how far the implementation of transparency and accountability principles of village chief in managing the Village Budget (APDes) at the village of Sidogedungbatu Sub-District of Sangkapura District of Gresik in the Village Allocation Fund (ADD) through the activities i.e.: the planning, the implementation, the reporting, and the responsibility. The descriptive which is done by using the qualitative approach is used as the research method. The informants of this research are the village chief, the management team of Village Allocation Fund of Sidogedungbatu village, Vice Chairman of Village Consultative Agency (BPD) and Community Representatives.The data collection technique has been done by conducting interview, observation, and documentation analysis. The data analysis technique has been done by organizing the data, simplifying of data, data analysis process and the result of interpretation.The result of the research shows that the village chief of Sidogedungbatu village Sub-District of Sangkapura District of Gresik has carried out the transparency and accountability principles to the management of Village Budget (APBDes) in 2013 budgetâs year. Generally, the transparency and accountability principles at the village of Sidogedungbatu Sub-District of Sangkapura District of Gresik has been running well, even though there are some weaknesses which need to be improved. suitable with the existing provisions.Keywords: Village Budget (APBDes), Village Allocation Fund, Transparency and Accountability.